Microfluidic paper-based analytical device (μPAD) for rapid detection of cadmium in river water - Aziz, Nor Izati Che Ab (2020)
In recent years, the issue of contamination of water with heavy metal ion is never-ending, thus seeking extensive attention from all over the world. Heavy metal above a threshold limit is toxic to humans as well as the environment. Therefore, a very promising method using μPAD is presented for the rapid determination of Cd at an ultra-trace level using 1,5-diphenylthiocarbazone (dithizone) as colorimetric reagent (λ=500 nm) in aqueous solution. The mixture turns from brownish-red to orange colour in the presence of Cd. The use of paraffin wax with the handheld rubber stamp was demonstrated for the detection of Cd using colorimetric detection. The paraffin wax was used onto the filter paper to create a hydrophobic barrier for fluidic channels. The μPAD was fabricated within 10 min and provided high reproducibility and stability. The rubber stamping method provides a simple, rapid and cost-effective in fabrication of uPAD. The calibration curves were constructed for developed method of μPAD. The linear coefficient (R2) was 0.9538 and the detection limits of Cd ion using μPAD was 3.87 ppm. The results demonstrate that the detection limits obtained for both methods were higher than the permissible limit of Cd which is 0.005 ppm. These methods were reported to be less sensitive for ultra-trace metal such as Cd. However, for real sample analysis, the recovery of Cd in the water samples was measured as 82.5% using μPAD. It has good recovery value. To conclude, the fabricated μPAD can be used as screening test which one of the most vital steps in paper-based assays to identify the presence of analyte but confirmation step is required for further analysis using the sophisticated instruments.